2010
DOI: 10.1007/s11695-010-0310-0
|View full text |Cite
|
Sign up to set email alerts
|

Intragastric Balloon Treatment for Obesity: Results of a Large Single Center Prospective Study

Abstract: Results of this large prospective single center study confirmed that intragastric balloon is useful and safe method for promoting weight loss. Due to improvement of metabolic parameters, treatment with BIB results in reduction of cardiovascular risk and provides a sustained benefit on liver function in obese patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
1
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 24 publications
1
33
1
3
Order By: Relevance
“…After 6 months, mean BMI was 31.1 ± 7.2 and mean %EWL reached 41.6 ± 21.8%. Similar results were confirmed by our group in a series of 171 patients [12]. The mean BMI during balloon treatment declined from 41.9 ± 7.3 to 36.0 ± 7.9 with %EWL of 39.7 ± 23.6%.…”
Section: Restrictive Endoscopic Proceduressupporting
confidence: 88%
“…After 6 months, mean BMI was 31.1 ± 7.2 and mean %EWL reached 41.6 ± 21.8%. Similar results were confirmed by our group in a series of 171 patients [12]. The mean BMI during balloon treatment declined from 41.9 ± 7.3 to 36.0 ± 7.9 with %EWL of 39.7 ± 23.6%.…”
Section: Restrictive Endoscopic Proceduressupporting
confidence: 88%
“…Patients in our study experienced only metabolic effects. Stimac et al [7] also demonstrated there that there were no significant differences in LDL and total cholesterol concentration.…”
Section: Discussionmentioning
confidence: 93%
“…A cinética da perda de peso foi avaliada em dois momentos e contextos distintos: após a remoção do balão e depois do periódo de follow-up (PFU), que variou entre 6-12 meses. Eficácia definida como perda de peso 10% após PFU de [6][7][8][9][10][11][12] 16 foram excluidos (7 por intolerancia) e 35 entraram no estudo, dos quais 83% foram seguidos durante PFU. A perda de peso média (PPM) e % de excesso de peso perdido (EPP) na altura de remoção do BIG foi de 11.94 kg e 42.16%, respetivamente; após PFU, a PPM foi de 8.25 kg e o EPP foi 30.27%.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Stimac et al [35] in prospective studies involving 171 patients after BIB confirmed the effectiveness of the procedure as a method of weight reduction, at the same time obtaining substantial improvement in blood pressure, glycaemia and triglycerides level. However, the reduction of total cholesterol and low-density lipoproteins, and the increase in high density lipoproteins were not observed.…”
Section: Discussionmentioning
confidence: 85%